SILENCE IS NOT GOLDEN - Mariska Febrianti; Bambang Suwarno (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
In order to improve students’ language skill various teaching methods need to be introduced in the language classroom. The aim of this paper was to investigate the effect of small group discussion on students’ achievement in grammar. This was a pre-experimental research, in which there was only an experiment group that was taught through small group discussion. The subjects consisted of the second semester Accountancy students at Dehasen University. The data were obtained from the students’ test scores. Data analysis showed that there was a significant difference between pre-test mean and post-test mean. Thus, it could be concluded that small group discussion technique could improve students’ grammar. This improvement could be contributed to more active students’ participation through small group discussion. Further study using quasi experiment is recomended